The attenuated Mycoplasma bovis strain promotes apoptosis of bovine macrophages by upregulation of CHOP expression - Zhang, Hui; Lu, Siyi; Chao, Jin; Lu, Doukun; Zhao, Gang; Chen, Yingyu; Chen, Huanchun; Faisal, Muhammad; Yang, Liguo; Hu, Changmin; Guo, Aizhen (Frontiers in Microbiology, 2022)
Mycoplasma bovis (M. bovis) is one of the most common infections in the bovine respiratory disease complex, which includes pneumonia, mastitis, and arthritis and causes a great economic loss in cattle industry. In China, a live attenuated vaccine strain M. bovis P150 was obtained by continuously culture of the wild type strain M. bovis HB0801 (P1) in vitro for 150 passages. Using the infected bovine macrophage cell line BoMac, this work attempted to investigate the mechanism of P150 attenuation and protective immune response. To begin, we show that M. bovis P150 effectively triggered cytotoxicity and apoptosis in bovine macrophages (BoMac), although with lower intracellular survival than P1. The transcriptomes of BoMac after infection with M. bovis strains P1 and P150 were sequenced, and bioinformatic analysis identified 233 differentially expressed genes (DEGs), with 185 upregulated and 48 downregulated. Further Gene Ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analyses revealed that the majority of the DEGs were linked to CHOP complex, MAP kinase phosphatase activity and were involved in the IL-17 signaling pathway in immune response, MAPK signaling pathway in signal transduction, and p53 signaling pathway in cell growth and death. Among them, the level of C/EBP homologous protein (CHOP) was significantly up-regulated in P150 infected BoMac compared to P1 infected cells at different time points, along with its upstream and downstream genes phosphorylated-PERK, phosphorylated-EIF2α, ATF4, and GADD45A increased in PERK-dependent ER stress response. The role of CHOP in apoptosis was further verified by M. bovis-induced siCHOP knockdown in BoMac cells. The results showed that CHOP knockdown enhanced P150-induced apoptosis and dramatically increased the M. bovis P1 and P150 intracellular survival, particularly for P150. These data suggest that P150 infection upregulates CHOP expression, which can increase apoptosis and mediate a crosstalk between ER stress and apoptosis during infection, and hence contribute to high cytotoxicity and low intracellular survival.